The Complex Etiology of Childhood Obesity in Arabs Is Highlighted by a Combination of Biological and Socio-Economic Factors - Elkum, Naser; Alarouj, Monira; Bennakhi, Abdullah; Shaltout, Azza (Frontiers in Public Health, 2019)
OBJECTIVES: To identify predictors of childhood and adolescent obesity in Kuwaitis with Arab ethnicity. METHODS: A cross-sectional sample of 618 year-old schoolchildren was randomly selected from 244 public schools across all six governorates in the State of Kuwait. Anthropometric data were measured from 6574 Arab Kuwaiti schoolchildren, and a structured questionnaire was used to collect information on possible risk factors associated with obesity. Overweight and obesity were defined in accordance with the Centre for Disease Control and Prevention criteria. RESULTS: The prevalence of overweight and obesity in children (aged 618 years) were 17.7% and 33.7%, respectively. The likelihood of childhood obesity increased with birth weights >4.0 Kg [odds ratio (OR) = 2.3; p <0.0001], maternal employment (OR = 1.26, p = 0.0006), maternal age at pregnancy > 30 years (OR = 1.24; p = 0.0016) and family size of less than six members (OR = 1.16, p = 0.0106). CONCLUSIONS: Public health professionals should be aware that advanced maternal age, maternal employment, smaller family size and high birthweight may predict the risk of obesity in Kuwaiti Arab children and adolescents.